Travelling-wave solutions for some fractional partial differential equation by means of generalized trigonometry functions - Hammouch, Zakia; Mekkaoui, Toufik (International Journal of Applied Mathematical Research, 2012)
Making use of a Fan's sub-equation method and the Mittag-Lefflerfunction with aid of the symbolic computation system Maple we construct a family of traveling wave solutions of the Burgers and the KdV equations. The obtained results include periodic, rational and soliton-like solutions.